2009
DOI: 10.1261/rna.1582609
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that U2/U6 helix I promotes both catalytic steps of pre-mRNA splicing and rearranges in between these steps

Abstract: During pre-mRNA splicing, the spliceosome must configure the substrate, catalyze 59 splice site cleavage, reposition the substrate, and catalyze exon ligation. The highly conserved U2/U6 helix I, which adjoins sequences that define the reactive sites, has been proposed to configure the substrate for 59 splice site cleavage and promote catalysis. However, a role for this helix at either catalytic step has not been tested rigorously and previous observations question its role at the catalytic steps. Through a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
105
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(113 citation statements)
references
References 49 publications
7
105
0
1
Order By: Relevance
“…At the catalytic stage of splicing, the spliceosome assumes two catalytic conformations and an intermediate conformation (17)(18)(19). Although Prp43p could conceivably discard splicing intermediates from any of these conformations, Prp43p may act inefficiently on the catalytic conformations, because Prp16p and Prp22p bind the first and second catalytic conformations, respectively (11,14,15,17,36), and Prp16p, Prp22p, and Prp43p appear to bind to the spliceosome mutually exclusively (37,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the catalytic stage of splicing, the spliceosome assumes two catalytic conformations and an intermediate conformation (17)(18)(19). Although Prp43p could conceivably discard splicing intermediates from any of these conformations, Prp43p may act inefficiently on the catalytic conformations, because Prp16p and Prp22p bind the first and second catalytic conformations, respectively (11,14,15,17,36), and Prp16p, Prp22p, and Prp43p appear to bind to the spliceosome mutually exclusively (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Prp22p, which promotes release of the mRNA after exon ligation (15,16), discriminates against mutated consensus sites before exon ligation (11). Fidelity is also promoted by the sequestration of suboptimal substrates through equilibration between distinct spliceosomal states (17)(18)(19).…”
mentioning
confidence: 99%
“…45 Furthermore, different cross-linking profiles of wt Brr2 and a variant exhibiting a residue exchange (G858R) in the NC 5 0 HP/separator loop with U6 snRNA 46 together with the latter variant exhibiting a second step defect and showing synthetic lethality with step 2 mutations in Slu7, Prp18 and Prp16 46,49 suggest that Brr2 participates in a transient opening of the catalytic core between the 2 steps of splicing, which is characterized by the intermittent disruption of U6-5SS and U2-U6 interactions. 125,126 However, whether Brr2 actively disrupts RNA-RNA or RNA-protein interaction in this phase of splicing or whether it simply provides RNA binding sites is presently unclear. 46 Curiously, the E909K exchange in Brr2 blocks splicing in extracts at or before the first catalytic step and leads to the appearance of an off-pathway spliceosomal particle following B complex formation, which lacks U4 and U5 snRNAs.…”
Section: Brr2 Regulation During Splicingmentioning
confidence: 99%
“…1 and 3). While the details of the basepairing interactions may be different in yeast and human spliceosomes [52][53][54] (Fig. 3), the general architecture of the U6/U2 basepaired complex is conserved.…”
Section: The Three Dimensional Positioning Of Snrnas In the Active Sitementioning
confidence: 99%
“…13,24,65 Using protein-free snRNAs, Yuan and colleagues 29 used a FRETbased assay that took advantage of the increase in the luminescence other in the folded, active structure of the U6/U2 complex found in the activated spliceosomes, perhaps in an arrangement similar to the one found in group II introns. 12,14 While several studies indicate that the transition from the first step of splicing to the second involves a conformational change, 54,[57][58][59] it is likely that the same three domains of U6 are involved in catalysis of both steps of splicing. Mutagenesis studies have suggested a critical role for all three regions in both the first and second steps of splicing.…”
Section: The Three Dimensional Positioning Of Snrnas In the Active Sitementioning
confidence: 99%